2022
DOI: 10.1111/jce.15495
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospital case volume on the outcomes after catheter ablation for atrial fibrillation according to the ablation technology

Abstract: Introduction:The appropriate hospital case volume for catheter ablation (CA) in patients with atrial fibrillation (AF) according to the ablation technology has not been fully examined. This study aimed to investigate the association between the hospital case volume for AF and periprocedural complications and AF recurrence. Methods: In this retrospective cohort study, we used data from the National Database of Health Insurance Claims and Specific Health Checkups, which covers almost all healthcare insurance cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recently published data from Japan's national database of healthcare insurance claims from 2014 to 2020 involving more than 270,000 de-novo AF ablations, showed an acute complication rate of 2%, similar to our study and acute procedural complications decreased significantly when hospital procedural volume approached 150-200/year. Interestingly, this volume-outcome effect was seen only for radiofrequency ablation, but not for cryoablation 23 . In our study, we did not stratify by ablation energy source as this was not an available variable in the registry, but this attenuated volume-outcome relationship with cryoablation may be due to less procedural and patient complexity and a potentially faster learning curve for hospital staff and physicians.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently published data from Japan's national database of healthcare insurance claims from 2014 to 2020 involving more than 270,000 de-novo AF ablations, showed an acute complication rate of 2%, similar to our study and acute procedural complications decreased significantly when hospital procedural volume approached 150-200/year. Interestingly, this volume-outcome effect was seen only for radiofrequency ablation, but not for cryoablation 23 . In our study, we did not stratify by ablation energy source as this was not an available variable in the registry, but this attenuated volume-outcome relationship with cryoablation may be due to less procedural and patient complexity and a potentially faster learning curve for hospital staff and physicians.…”
Section: Discussionmentioning
confidence: 94%
“…The optimal procedural volumes for hospitals and physicians are not clear, and various studies have suggested volume thresholds for hospitals and physicians of 100-200 and 25-100 per year, respectively 11,12,17,19,20,22,23 . Based on our current study, hospitals and physicians performing approximately 190 and 60 annual cases, respectively, are likely to contribute to consistently high procedural success (>98%) and safety (MAE <1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation